AKSENTUASI TEKNOLOGI KINERJA GURU PROFESIONAL - Hambali Hambali (Nurul Jadid University, 2016)
Global competition has demanded thorough changes of significance. In fact, in the world of education today. The complexity of suspected learning problems due to low resources and the role of the teacher as the cutting edge of learning. Teachers rated begin to lose touch pedagogic and profes- sionalism of its qualified. Therefore, the emphasis on the main components of this study need to be raised through some form of education and training is expected to make the teacher as a profession that works in a systematic and structured. The teacher as a facilitator of learning are ideally required to be able to determine the learning strategies, develop syllabi proges to measure the learning progress of students.